Sorne strategies used by Peruvian families to cope with the present socioeconomic crisis - Majluf, Alegria (1994)
This study focuses on srraregies used by mothers of middle and low SES ro cope with the present socioeconomic crisis. Using a brief quesrionnaire and rhe F-Copes Scale, 20 morhers from each socioeconomic leve! were interviewed. Resulrs showed rhar borh gro\lpS were affected economically and rook measures ro reduce rheir expenses in basic needs such as food, clorhing and recreation. Morhers coming from rhe middle SES used estategies ro reestructure che situation and make ir more bearable, while mothers from low SES were more passive and relied on rheir extended families. No differences were found in rheir search for spiritual and social support.